2011
DOI: 10.5194/nhess-11-1901-2011
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on earthquake and ground based transmitter induced radiation belt electron precipitation at middle latitudes

Abstract: Abstract.We examined (peak-to-background flux ratio p/b > 20) energetic electron bursts in the presence of VLF activity, as observed from the DEMETER satellite at low altitudes (∼700 km). Our statistical analysis of measurements during two 6-month periods suggests that: (a) the powerful transmitter NWC causes the strongest effects on the inner radiation belts in comparison with other ground-based VLF transmitters, (b) the NWC transmitter was responsible for only ∼1.5 % of total electron bursts examined during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…These longer time differences are in agreement with the latest DEMETER IDP findings, where increases in energetic electron fluxes were observed a few days before earthquakes (Anagnostopoulos et al, 2010a, b;Sidiropoulos et al, 2011). Based on this, we set out to verify by how many and how high EBs increased prior to strong earthquakes over the entire DEMETER IDP survey period from 2005 to 2010.…”
Section: Summary Of Earthquakes With M ≥ 70supporting
confidence: 77%
See 1 more Smart Citation
“…These longer time differences are in agreement with the latest DEMETER IDP findings, where increases in energetic electron fluxes were observed a few days before earthquakes (Anagnostopoulos et al, 2010a, b;Sidiropoulos et al, 2011). Based on this, we set out to verify by how many and how high EBs increased prior to strong earthquakes over the entire DEMETER IDP survey period from 2005 to 2010.…”
Section: Summary Of Earthquakes With M ≥ 70supporting
confidence: 77%
“…A possible model for describing high energy particle precipitation associated with seismic activity might include ultra-low frequency (ULF) and very low frequency (VLF) electromagnetic emissions (EME), which have been reported to be generated in seismic regions and are believed to propagate upwards into the atmosphere, ionosphere and even into the magnetosphere (Molchanov and Majaeva, 1994;Pulinets and Boyarchuk, 2004;Sidiropoulos et al, 2011). In fact, the magnetosphere is characterised by regions that are filled with charged particles trapped in the geomagnetic field, known as Van Allen belts (VAB) (McIlwain, 1966).…”
Section: Introductionmentioning
confidence: 99%
“…The calculated time differences between CRs by IDP and EQs were longer than those of previously published works, and increases in energetic electron fluxes were observed a few days before EQs (Anagnostopoulos et al, 2010), accompanied by broadband kHz emissions (Anagnostopoulos et al, 2012;Zhang et al, 2012) and compared to the VLF transmitter contributions (Sidiropoulos et al, 2011;Sauvad et al, 2014). Furthermore, a statistical similarity between high energy charged particle fluxes detected by DEMETER and EQs has also been reported (Wang et al, 2014).…”
Section: Introductionmentioning
confidence: 77%
“…In general, whistlers with high dispersion come from the opposite hemisphere or are due to whistlers going several times back and forth in the magnetosphere (Hayakawa et al, 1993;Elie et al, 1999). In fact, ELF and VLF waves are related not only to lightning but also to earthquakes (Pulinets and Boyarchuk, 2004;Athanasiou et al, 2011;Sidiropoulos et al, 2011;Anagnostopoulos et al, 2012). Hayakawa et al (1993) statistically examined whistlers at low latitudes and found that whistlers with anomalous dispersions are likely to be closely correlated with M = 6.0 earthquakes.…”
Section: Introductionmentioning
confidence: 99%